Niemieckie dziedzictwo kulturowe na łamach Informatora Muzeum Ziemi Lubuskiej w Zielonej Górze "Museion" = German cultural heritage in the pages of "Museion", the information guide of the Lubusz Land Museum in Zielona Gora - Polak, Alina (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The Information Guide of the Museum of the Lubusz Region in Zielona Góra, "Museion", has the task of disseminating up-to-date information on the Museum?s activities: exhibitions, research and different undertakings of its employees. In addition, there are texts presenting various aspects of the history of the Zielona Góra and the region, and the history of art. The author reviews the articles, exhibits, exhibitions, events and activities of the Museum and other regional cultural institutions, contributing to the collection, protection, research and popularization of the widely understood German cultural heritage.
Keywords: czasopisma; muzea; muzealnictwo; Museion (czasopismo); Muzeum Ziemi Lubuskiej; dziedzictwo kulturowe; Niemcy; magazines; museums; museology; cultural heritage; Germans